Rigidity of the affected femurs with systems of surgical treatment - N. Shidlovskiy; M. Dyman; A. Ilnitsky; V. Shytikov (Mechanics and Advanced Technologies)
Purpose. Subject matter of the present paper is to investigate the characteristics of rigidity and reliability of fixing of pathological changes at metastatic defeat are investigated in real, including cyclic, the modes of influence of external loadings. Design/methodology/approach. During experiment was used of extremities without pathology of a bone tissue and with a tumor on a bone tissue . Fixing of bone fragments (osteosynthesis) has been executed by means of the device of external fixing of A. Kostiuk and by means of reinforcing of a metal osteosynthesis by system with application of a extramedullar plate and bone cement. Tests were carried out, transferring freight on the fixed femur fragment change diversely. Ways of loadings: compression, a bend and rotation and cyclically variable freights which model human weight. Results. The reinforced metal osteosynthesis with application of a extramedullar plate and bone cement is more stable method of fixing in comparison with rod devices of external fixing like AVF-K. Fixing of a change in the way of a metal osteosynthesis significantly interferes with development of deformations at action of cyclic loadings. Is the most dangerous from the point of view of physiological reliability for both studied systems of an osteosynthesis bending and rotational loadings. Originality/cost. Results are important for medicine and can improve treatment.